The child play behavior and activity questionnaire: A parent-report measure of childhood gender-related behavior in China - Yu, L.; Winter, Sam; Xie, D. (SPRINGER/PLENUM PUBLISHERS, 2010)
Boys and girls establish relatively stable gender stereotyped behavior patterns by middle childhood. Parent-report questionnaires measuring children's gender-related behavior enable researchers to conduct large-scale screenings of community samples of children. For school-aged children, two parent-report instruments, the Child Game Participation Questionnaire (CGPQ) and the Child Behavior and Attitude Questionnaire (CBAQ), have long been used for measuring children's sex-dimorphic behaviors in Western societies, but few studies have been conducted using these measures for Chinese populations. The current study aimed to empirically examine and modify the two instruments for their applications to Chinese society. Parents of 486 Chinese boys and 417 Chinese girls (6-12 years old) completed a questionnaire comprising items from the CGPQ and CBAQ, and an additional 14 items specifically related to Chinese gender-specific games. Items revealing gender differences in a Chinese sample were identified and used to construct a Child Play Behavior and Activity Questionnaire (CPBAQ). Four new scales were generated through factor analysis: a Gender Scale, a Girl Typicality Scale, a Boy Typicality Scale, and a Cross-Gender Scale (CGS). These scales had satisfactory internal reliabilities and large effect sizes for gender. The CPBAQ is believed to be a promising instrument for measuring children's gender-related behavior in China. © 2008 Springer Science+Business Media, LLC.